H12‐(ADP)‐liposomes for hemorrhagic shock in thrombocytopenia: Mesenteric artery injury model in rabbits. Issue 2 (15th February 2022) - Hagisawa, Kohsuke; Kinoshita, Manabu; Takeoka, Shinji; Ishida, Osamu; Ichiki, Yayoi; Saitoh, Daizoh; Hotta, Morihiro; Takikawa, Masato; Torres Filho, Ivo P.; Morimoto, Yuji
Abstract: Background: Damage control resuscitation improves patient outcomes after severe hemorrhage and coagulopathy. However, effective hemostasis methods for these critical situations are lacking. Objective: We evaluated the hemostatic efficacy of fibrinogen γ‐chain (HHLGGAKQAGDV, H12)‐coated, adenosine‐diphosphate (ADP)‐encapsulated liposomes (H12‐[ADP]‐liposomes) in thrombocytopenic rabbits with hemorrhagic shock. Methods: Acute thrombocytopenia (80%) was induced in rabbits that also received mesenteric vessel injury, leading to hemorrhagic shock. Five minutes after injury, subjects received intravenous bolus injection with H12‐(ADP)‐liposomes (20 mg/kg), followed by isovolemic transfusion with stored red blood cells (RBCs)/platelet poor plasma (PPP) (RBC:PPP = 1:1 [vol/vol]), or lactated Ringer solution every 5 min to compensate blood loss. One group received H12‐(phosphate buffered saline [PBS]) liposomes followed by RBC/PPP. Additional groups were received isovolemic transfusion with RBC/platelet rich plasma (PRP) (RBC:PRP = 1:1 [vol/vol]), RBC/PPP, PPP alone, or lactated Ringer solution. Results: Treatment with H12‐(ADP)‐liposomes followed by RBC/PPP transfusion and RBC/PRP transfusion effectively stopped bleeding in all thrombocytopenic rabbits. In contrast, three of 10 rabbits treated with RBC/PPP failed hemostasis, and no rabbits receiving lactated Ringer solution stopped bleeding or survived. Twenty‐four hours after hemorrhage, 80% of rabbits receiving H12‐(ADP)‐liposome followed by RBC/PPP transfusion survived and 70% of rabbits receiving RBC/PRP transfusion also survived, although RBC/PPP‐transfused rabbits showed 40% survival. Rabbits receiving H12‐(ADP)‐liposomes followed by lactated Ringer solution showed a transient hemostatic potential but failed to survive. H12‐(PBS)‐liposomes showed no beneficial effect on hemostasis. Neither the PPP group nor the lactated Ringer group survived. Conclusion: H12‐(ADP)‐liposome treatment followed by RBC/PPP may be effective in lethal hemorrhage after mesenteric vessel injury in coagulopathic rabbits.